KAJIAN MORFOLOGI DAN KARAKTERISTIK FAMILI RUBIACEAE BERDASARKAN STUDI LITERATUR - Hosyanna Situmorang; Icha Indah Wardani; Laura Capenesi Simanjuntak; Tri Wahyuni; Heppy Setya Prima (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Rubiaceae is one of the flowering plant families with high species diversity and wide distribution in tropical and subtropical regions. However, comprehensive studies discussing the morphological and anatomical characteristics of Rubiaceae are still limited. This study aimed to examine the general morphological characteristics, anatomical features, adaptive functions, and potential uses of Rubiaceae based on literature studies. The research employed a qualitative descriptive method with a literature study approach using scientific journals, books, and relevant academic references as data sources. The collected data were analyzed descriptively by comparing and classifying information regarding stem, leaf, flower, fruit, and anatomical characteristics of several Rubiaceae species. The results showed that Rubiaceae generally possesses opposite single leaves with stipules, woody stems, compound flowers with diverse colors, and varied fruit forms. Anatomical characteristics such as epidermal structure, stomata, trichomes, and pollen morphology also support the identification and classification of this family. Morphological variation among species reflects adaptation to environmental conditions and habitat diversity. In addition, many Rubiaceae species have important economic and ethnobotanical values as medicinal plants, ornamental plants, food sources, and industrial materials. Therefore, the study of Rubiaceae morphology provides important scientific information that can support botanical studies, taxonomy, conservation, education, and sustainable utilization of plant resources.